Determination of the obesity status of patients who came a family health center in Turkey - OĞUZ, SIDIKA; ÇAMCI, GÜLŞAH (My University, 2017)
Topic: Obesity Backgorund: An increased consumption of highly calorific foods, without an equal increase in physical activity, leads to an unhealthy increase in weight. Obesity causes a lot of diseases Purpose : The research was performed to determine the obesity status of patients who came a family health center in Istanbul/Turkey Method: The research was performed by totaly 159 patients betwen the dates 17th-18th October 2016 in a family health center in Istanbul/Turkey. Patients over the age of 18 who were willing to work and have open consciousness were enrolled. Date were collected using a questionnaire which was composed by researchers’s examining the literatures. Data were analyzed by using frequency, percentage, mean and chi square overweight 44%; normal weight 38,6%. Conclusions: Girls with obesity and overweight had elevated consumption of fats and carbohydrates and increased food caloric value in their diet. During investigation we found high prevalence of obesity and overweight in girls’ parents belonging to the main group in comparison with the control one which may increase the risk of obesity development in their children in future. Considering the high intensity metabolism of adolescents demanding exceedence of incoming energy over spent one and also family obesity factor opens new opportunities towards prevention of this disease.